Peran Gereja dalam Membentuk Karakter Remaja Kristen di Era Kontemporer - Gea, Erniwati; Waruwu, Anwar Three Millenium; Novalina, Martina; Rohy, Ampinia Rahap Wanyi (Sekolah Tinggi Teologi Nusantara, 2023)
The education of adolescent character plays a significant role in shaping a future generation that is robust and responsible. In this contemporary era, replete with various challenges, sturdy character and strong moral values stand as essential foundations required by Christian adolescents. The church assumes a strategic role in ensuring the balanced and ethical development of adolescent character. This research aims to analyze the church's contribution as an effective partner for parents in molding adolescent character, as well as how character education within the church can cater to the individual needs of each adolescent in the contemporary era. The methodology employed in this study is a literature review, involving the extraction of information from diverse literary sources such as books, documents, magazines, journals, and newspaper publications. The research findings indicate that the roles of the church, family, and community are paramount in providing support, education, and guidance to Christian adolescents in facing challenges like technological influence and negative temptations. Collaboration between the church, family, school, and relevant institutions emerges as the linchpin in shaping the character of Christian adolescents. Through a pertinent and inclusive approach, Christian adolescents can grow in faith and become stalwart successors for the nation and the church in the future. Abstrak:Pendidikan karakter remaja memegang peran penting dalam membentuk generasi masa depan yang kuat dan bertanggung jawab. Di era kontemporer yang penuh dengan berbagai tantangan, karakter yang kokoh dan nilai-nilai moral yang kuat adalah fondasi utama yang dibutuhkan oleh remaja Kristen. Gereja memiliki peran strategis dalam memastikan pertumbuhan karakter remaja yang seimbang dan beretika. Penelitian ini bertujuan untuk menganalisis kontribusi gereja sebagai mitra efektif bagi orang tua dalam membentuk karakter remaja, serta bagaimana pendidikan karakter di gereja dapat memenuhi kebutuhan individu masing-masing remaja di era kontemporer. Metode kajian pustaka digunakan dalam penelitian ini, dengan menggali informasi dari berbagai sumber literatur seperti buku, dokumen, majalah, jurnal, dan publikasi surat kabar. Hasil penelitian menunjukkan bahwa peran gereja, keluarga, dan komunitas sangat vital dalam memberikan dukungan, pendidikan, dan bimbingan kepada remaja Kristen dalam menghadapi tantangan-tantangan seperti pengaruh teknologi dan godaan-godaan negatif. Kerjasama antara gereja, keluarga, sekolah, dan lembaga terkait menjadi kunci dalam membentuk karakter remaja Kristen. Dengan pendekatan yang relevan dan inklusif, remaja Kristen dapat tumbuh dalam iman dan menjadi penerus yang kuat bagi bangsa dan gereja di masa depan.Kata Kunci: Pendidikan Karakter, Remaja Kristen, Peran Gereja, Era Kontemporer.